2021
DOI: 10.3389/fcell.2021.616888
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide and Reduced Graphene Oxide Exhibit Cardiotoxicity Through the Regulation of Lipid Peroxidation, Oxidative Stress, and Mitochondrial Dysfunction

Abstract: ObjectiveGraphene has been widely used for various biological and biomedical applications due to its unique physiochemical properties. This study aimed to evaluate the cardiotoxicity of graphene oxide (GO) and reduced GO (rGO) in vitro and in vivo, as well as to investigate the underlying toxicity mechanisms.MethodsGO was reduced by gamma irradiation to prepare rGO and then characterized by UV/visible light absorption spectroscopy. Rat myocardial cells (H9C2) were exposed to GO or rGO with different absorbed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…A study on H9C2 rat myocardial cells showed an increasing level of LDH while testing higher concentrations for rGO with respect to GO. It is relevant to declare that the average size of GO and rGO was in the order of 200 nm [ 58 ]. In another study, a better performance was shown by rGO with respect to GO when dealing with the same size (0.4–0.8 µm).…”
Section: Resultsmentioning
confidence: 99%
“…A study on H9C2 rat myocardial cells showed an increasing level of LDH while testing higher concentrations for rGO with respect to GO. It is relevant to declare that the average size of GO and rGO was in the order of 200 nm [ 58 ]. In another study, a better performance was shown by rGO with respect to GO when dealing with the same size (0.4–0.8 µm).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the other form of graphene can affect cell receptors and disrupt metabolism by inhibiting glucose or amino acid supply, which leads to the induction of endoplasmic reticulum (ER) stress, apoptosis or autophagy. Moreover, graphene itself can bind intracellular nutrients from the cell culture medium, which limits their availability and inhibits cellular proliferation and viability [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Graphene (G) and its derivatives, referred to as nanomaterials from the graphene family (GFNs), include graphene oxide (GO), its reduced form (rGO), single-or few-layer graphene, graphene nanosheets (GNS), and graphene nanoribbons [4,5]. However, the most important chemical derivative of graphene is GO.…”
Section: Introductionmentioning
confidence: 99%
“…Mittali et al [ 47 ] also noted that unoxidized, thermally reduced GO induces higher viability reduction in comparison to GO. Some studies show that the gradually increasing total ROS content was exhibited in cells with GO or rGO treatment [ 48 ]. However, Gurunathan et al [ 43 ] presented that the level of ROS production was significantly higher in rGO-treated cells than in GO-treated cells.…”
Section: Resultsmentioning
confidence: 99%